Validation of the COVID-19 Fear Scale modified for application during the perinatal period - Alejandro Irvin Soto Briseño; Rita A. Gomez-Diaz; Ricardo Cesar Saldaña Espinoza; Pilar Lavielle; Adriana Leticia Valdez González; Niels H. Wacher (Taylor & Francis Group, 2022)
Purpose The COVID-19 Fear Scale (FCV-19S) allows screening in general population; however, there is no specific instrument in our population for screening in the perinatal period that considers fear related with COVID-19 and offspring well-being. We aimed to validate the FCV-19S modified for application during the perinatal period. Materials and methods Analytical, cross-sectional design. After signing consent, women 18-45 years were included. Internal consistency was calculated with Cronbach's alpha, external validity using the Hospital Anxiety and Depression Scale (HADS), factorial analysis and intraclass correlation coefficient for re-test. Results The sample included 178 women, mean age 31.04 ± 5.9. We obtained internal consistency with Cronbach's alpha = 0.873 (95%CI, 0.842-0.899). Spearman's Rho coefficient was 0.207 (p= .013). All the elements were statistically significant for the polychoric correlation (p<.001). Reliability test-retest with intraclass correlation was 0.873. Conclusions The version of FCV-19S modified with eight items is a valid measurement instrument for application during the perinatal period, showing adequate internal consistency and external validity with HADS as measure of concurrence to identify anxiety related with COVID-19 during the perinatal period.